Strategi Negara menghadapi Foreign Terrorist Fighter Returnees sebagai Ancaman Transnasional (Studi pada Kebijakan Indonesia Periode 2014-2019) - Gustarina, Fauzia; Akbar, Taufiq (Interdependence Journal of International Studies, 2020)
After the defeat of the Islamic State of Iraq and Syria (ISIS) by US coalition in the city of Baghouz, Foreign Fighters (FF) who were members of ISIS surrendered and captured by Syrian Democratic Forces (SDF), led to the wave of Returnees of FF one of which came to Indonesia. The purpose of this study is the realization of the government's strategy in dealing with FF Returnees in Indonesia. This study uses a qualitative method with a phenomenological approach. Data collection through interviews, observations and document studies and then analyzed with Miles, Huberman and Saldana analysis techniques. This study used the theory of strategy and the concept of threats whose results show that the threat of FF Returnees in Indonesia are military capabilities, international networks, the transfer of Dar Harb, lone wolf attacks, and ideology. In order to prevent this the government prepared a multi-layered categorization and verification strategy. Law enforcement will be carried out in accordance with Law No. 5 of 2018, and a deradicalization program will be carried out on FF Returnees.